Membangun Budaya Riset di Sekolah: Pelatihan PTK Untuk Guru Dalam Meningkatkan Kualitas Pembelajaran - Mulyati, Sri; Iskandar; Nuryatin, Atin; Putri, Ermalia; Radesa, Jingga (Kreativasi : Journal of Community Empowerment, 2025)
Most teachers do not yet have adequate knowledge of the concepts, methodologies, and stages of PTK. This causes them difficulty in designing and implementing systematic research to improve the learning process in the classroom. The purpose of the activity is to improve teachers' understanding and skills in identifying learning problems and designing reflective improvement actions through training PTK. The implementation methods include socialization, training, technology application, mentoring, and evaluation, as well as ensuring the sustainability of the program. Based on the post-test results conducted after the activity, it was found that there was a significant improvement in teachers' understanding of the concepts and steps in designing Classroom Action Research (PTK). The majority of participants were able to systematically design PTK plans relevant to the learning issues in their respective classrooms. These results indicate that the training successfully equipped teachers with the basic skills needed to integrate research into teaching practices to improve the quality of education.